Obligate herbivory in an ancestrally carnivorous lineage: the giant panda and bamboo from the perspective of nutritional geometry. (1st July 2014) - Nie, Yonggang; Zhang, Zejun; Raubenheimer, David; Elser, James J.; Wei, Wei; Wei, Fuwen
Summary: Herbivores face various nutritional challenges in their life cycles, challenges that may become increasingly acute under ongoing environmental changes. Here, focusing on calcium, phosphorus and nitrogen, we used nutritional geometry to analyse individual‐based data on foraging and extraction efficiencies, and combined these with data on reproduction and migratory behaviour to understand how a large herbivorous carnivore can complete its life cycle on a narrow and seemingly low quality bamboo diet. Behavioural results showed that pandas during the year switched between four main food categories involving the leaves and shoots of two bamboo species available. Nutritional analysis suggests that these diet shifts are related to the concentrations and balances of calcium, phosphorus and nitrogen. Notably, successive shifts in range use and food type corresponded with a transition to higher concentrations and/or a more balanced intake of these multiple key constituents. Our study suggests that pandas obligatorily synchronize their seasonal migration and reproduction with the disjunct nutritional phenologies of two bamboo species. This finding has potentially important implications for habitat conservation for this species and, more generally, draws attention to the need for understanding the nutritional basis of food selection in devising management plans for endangered species. Abstract : Lay Summary